The importance of long-term hygrothermal assessment of museum spaces: method and application in a permanent exhibition in a historical building - Pereira, Luísa Dias (2019)
This paper presents the analysis of the hygrothermal conditions of a museum space hosted in an 18th century building, in Coimbra (Portugal). This historical building, which houses the Science Museum of the University of Coimbra, is located in the historic centre of the University of Coimbra, officially declared a World Heritage Site in 2013 by UNESCO. The methodology proposed in EN 15757:2010 was applied to two monitoring campaigns carried out at a distance of 4 years, in two of the rooms of the permanent exhibition. The results of the monitoring periods are presented and discussed. The findings unveil the necessity for long-term monitoring of the indoor environmental conditions of museum spaces, towards the support of grounded based-evidence guidelines for the conservation of objects and quality of environment for exhibits conservation.